ICT-Based Language Learning Strategy ESL/EFL: A Meta-Analysis in Developing Classroom Language Activities through Gamification - Danny Gandana Nugraha; Bahtera Sembiring (Jurnal Bahasa Inggris Terapan, 2022)
The rapid advancement of technology has made a significant change in English Language learning, especially with the use of a number of various social media applications. The learning process merges along with the communication activities and has resulted in the integration of the four language skills through multi-mode. The study is aimed at attempting to investigate how this could bring a positive contribution to the development of English Language Teaching strategy. The study has been conducted through the results of a number of journal articles across different non-English-speaking countries and digital articles. The result indicates that gamification is the potential to boost language use in active communicative interaction in the classroom.